Cloud-to-ground lightning polarity and environmental conditions over the central United States - Kalb, Christina P., author; Rutledge, Steven A., advisor; Cotton, William R., committee member; Robinson, Steven R., committee member (Colorado State University. Libraries, 2007)
The majority of cloud-to-ground (CG) lightning across the United States lowers negative charge to the ground. However, recent studies have documented storms that produce an abundance of positive CG lightning. These positive storms have been shown to occur in different mesoscale regions on the same days, and in different thermodynamic environments. This study uses radar data, and CG lightning data, to identify positive and negative storms that occurred in the region between the Rocky Mountains and the Mississippi River. The thermodynamic conditions in the environment of these storms are derived from the Rapid Update Cycle model analysis, where the point nearest to the storm, in the direction of storm motion was used. Considerable scatter was present in the final results that limited the extent of the trends seen. Out of all the variables used, cloud base height, dew point, 850-500 mb lapse rate, and warm cloud depth showed the most difference between the positive and negative storms. Positive storms tended to occur with lower cloud base heights, higher dew points, smaller 850-500 mb lapse rates, and lower warm cloud depths. Little trend was seen for CAPE, CIN, freezing level, lifted index, mean relative humidity, mid-level relative humidity, precipitable water 0-3 km wind shear, 0-6 km wind shear, storm relative helicity, and Se. The strength of the differences seen between the positive and negative storms varies with the choice of percent positive used. Differences between the positive and negative storms tended to decrease when 10% was chosen (as compared to 30%), but they increased when 50% was chosen.
Related to Atmospheric science papers (Bluebooks).